Factors associated with dental anxiety and attendance in middle-aged and elderly women - Ha¨gglin C, Hakeberg M, Ahlqwist M, Sullivan M, Berggren U (Blackwell Synergy, 2000)
The aim of this study was to analyze the association between dental anxiety, dental attendance, health status and social factors. Our previous studies have shown that dental anxiety declines with age and is associated with poor oral health. In addition, correlations between dental anxiety, dental utilization and dental status have been revealed. However, the association of these factors with general health and social factors has not been analyzed in our previous studies.